Sea cucumber (Acaudina leucoprocta) peptides extended the lifespan and enhanced antioxidant capacity via DAF-16/DAF-2/SOD-3/OLD-1/PEPT-1 in Caenorhabditis elegans - Wu, Yue; Yang, Jingjuan; Xu, Chengmei; Li, Qiuqi; Ma, Yage; Zhao, Shenglan; Zhuang, Jiachen; Shen, Fei; Wang, Qianqian; Feng, Fengqin; Zhang, Xi (Frontiers in Nutrition, 2022)
The sea cucumber peptides (SCPs) from Acaudina leucoprocta were derived from the patented bio-enzyme digestion technology and the molecular weight of obtained SCPs was < 10 kDa. In this study, we investigated the possible anti-aging effects of SCPs on the model of Caenorhabditis elegans and the underlying mechanisms. SCPs extend the average lifespan of nematodes by 31.46%. SCPs enhance the anti-stress capacity of C. elegans by improving heat resistance and mobility, Also, the accumulated potential oxidative stress inducers like lipofuscin and reactive oxygen species (ROS) were reduced to 40.84 and 71.43%. In addition, SCPs can increase the antioxidant capacity in nematodes by enhancing the activity of SOD and CAT and reducing MDA accumulation in nematodes to 32.44%. Mechanistically, SCPs could mediate DAF-16/DAF-2/SOD-3/OLD-1/PEPT-1 axis to improve antioxidant capacity and extend lifespan in nematodes. Taken together, these findings provide a direction for the anti-aging effects of sea cucumber peptides and new insights into the further purifications of SCPs and future research on aging.